Preventive Inflammation Management with Steroids before Retreatment with Anti-VEGF after Severe Inflammation due to Brolucizumab - Karmy, Badiaa El; Castro, Daniela Gallo; Ambresin, Aude (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose We report two successful cases of treatment by steroids after severe inflammation due to an intravitreal injection (IVI) of brolucizumab and their retreatment with another type of anti-vascular endothelial growth factor (VEGF), with steroid treatments to prevent severe inflammatory recurrence in patients with exudative age-related macular degeneration (AMD).Clinical Cases, Case 1 An 88-year-old woman with exudative AMD in her left eye who had persistent subretinal fluid despite receiving an IVI, including ranibizumab and, subsequently, aflibercept. A switch to brolucizumab was decided. Two weeks after the third dose, she had a visual loss decreasing from 20/40 to counting fingers at 50 cm. Fundus examination revealed retinal whitening and perivenous sheathing. Fluoresceine angiography confirmed retinal arterial occlusion. Differential diagnoses were ruled out. She was treated with intravenous methylprednisolone and prednisolone eye drops. Three months after the treatment, visual acuity improved to 20/80 with no intraocular inflammation but subretinal fluid recurred. IVI of ranibizumab was rescheduled with preventive treatment by oral and local prednisolone without any inflammation recurrence.Case 2 An 80-year-old man with exudative AMD in his right eye who had persistent subretinal fluid despite an IVI of aflibercept. Switching him to brolucizumab was decided. Two months after the third dose, he had blurred vision with no pain. Visual acuity decreased from 20/20 to 20/25. Examination showed 1+ anterior chamber cells and hyalitis. We confirmed the diagnosis of anterior uveitis with hyalitis. Differential diagnoses were ruled out. Treatment by prednisolone eye drops was initiated every 30 minutes for 1 day with a gradual decrease for 6 weeks. One week later, visual acuity improved to 20/20 with no inflammation. Three weeks later, subretinal fluid due to AMD increased. The patient was retreated by aflibercept with prednisolone eye drops, 48 hours before and after the IVI, with no recurrence of inflammation.Discussion Brolucizumab is one of the latest FDA-approved anti-VEGF agents for wet AMD. Since its wider use, few cases of severe ocular inflammation have been reported in post-marketing analysis. Because wet AMD recurrences should be expected after intraocular inflammation, insight is needed into treatment tolerance in cases that received further IVI retreatment.Conclusion Our cases demonstrate that an IVI reinjection with a different anti-VEGF drug for exudative AMD recurrence can be safely reperformed. The use of local steroids could be effective in preventing recurrence of ocular inflammation after severe intraocular inflammation due to brolucizumab.
Keywords: retina; pharmacology; intraocular inflammation